Analysing Irish Prosody: a dual linguistic/quantitative approach - NI CHASAIDE, AILBHE; GOBL, CHRISTER (My University, 2004)
A project of Irish prosody is described which attempts to provide not only the basis for a linguistic description of the prosody of Irish dialects, but also the prerequisite quantitative characterization that is needed to allow us to use it for future technological applications, particularly text-to-speech development for Irish dialects. As with many other minority languages, there are particular challenges, but also particular opportunities to address. A multi-layered analytic approach is adopted, which will provide coverage of the three phonetic dimensions of prosody: pitch dynamics (intonation); voice quality; and temporal features. It is also envisaged that these analyses will provide the basis for an account that encompasses both the narrowly linguistic functions of prosody and its paralinguistic function of signaling attitude and emotion. In these last respects, this study aims also to contribute to the broader understanding of prosody, and to its modeling for more expressive speech synthesis. Given the relatively threatened status of Irish, we hope that by gearing our linguistic analysis to eventual technology exploitation, we can go beyond the mere documentation and aspire to the provision of tools that can support language teaching/learning and language usage generally.
Proceedings of the SALTMIL Workshop at LREC2004: First Steps in Language documentation for Minority Languages
LREC2004: First Steps in Language documentation for Minority Languages
PUBLISHED
Lisbon
Keywords: Computer science